Effects of Tobacco Usage and Antiretroviral Therapy on Biomarkers of Systemic Immune Activation in HIV-Infected Participants - Steel, Helen C.; Venter, W. D. Francois; Theron, Annette J.; Anderson, Ronald; Feldman, Charles; Kwofie, Luyanda; Cronjé, Tanita; Arullapan, Natasha; Rossouw, Theresa M. (Mediators of Inflammation, 2018)
Like HIV infection, smoking, which is common among HIV-infected persons, is associated with chronic, systemic inflammation. However, the possible augmentative effects of HIV infection and smoking and other types of tobacco usage on indices of systemic inflammation and the impact of combination antiretroviral therapy (cART) thereon remain largely unexplored and represent the focus of the current study. Of the total number of HIV-infected persons recruited to the study (n=199), 100 were categorised as pre-cART and 99 as virally suppressed (HIV viral load<40 copies/mL). According to serum cotinine levels, 144 and 55 participants were categorised as nonusers and users of tobacco, respectively. In addition to cytokines (IL-6, IL-8, and TNF-α) and chemokines (IP-10, MIG, IL-8, MCP-1, and RANTES), other biomarkers of systemic inflammation included C-reactive protein (CRP), β2-microglobulin, and those of neutrophil activation [ICAM-1, L-selectin, matrix metalloproteinase-9 (MMP-9)], microbial translocation (soluble CD14, LPS-binding protein), and oxidative stress (cyclophilin A, surfactant D). These were measured using multiplex bead array, ELISA, and immunonephelometric procedures. Viral suppression was associated with significant decreases in the levels of most of the biomarkers tested (P<0.0037-0.0008), with the exceptions of CRP, cyclophilin A, and MMP-9. With respect to tobacco usage, irrespective of cART status, circulating levels of β2-microglobulin, cyclophilin A, and RANTES were significantly elevated (P<0.042-0.012) in users vs nonusers. Additional analysis of the groups of tobacco users and nonusers according to cART status revealed high levels of RANTES in pre-cART/tobacco users relative to the three other subgroups (P<0.004-0.0001), while more modest increases in cyclophilin A and MMP-9 (P<0.019-0.027) were observed in comparison with the cART/tobacco user subgroup. Notwithstanding the efficacy of cART in attenuating HIV-associated, chronic systemic inflammation, the current study has identified RANTES as being significantly and seemingly selectively increased in those with active HIV infection who use tobacco, a mechanism which may underpin augmentative proinflammatory activity.